Synthesis of Large Surface‐Area g‐C3N4 Comodified with MnOx and Au‐TiO2 as Efficient Visible‐Light Photocatalysts for Fuel Production. Issue 3 (21st September 2017) - Raziq, Fazal; Sun, Liqun; Wang, Yuying; Zhang, Xuliang; Humayun, Muhammad; Ali, Sharafat; Bai, Linlu; Qu, Yang; Yu, Haitao; Jing, Liqiang
Abstract: Herein, this study successfully fabricates porous g‐C3 N4 ‐based nanocomposites by decorating sheet‐like nanostructured MnO x and subsequently coupling Au‐modified nanocrystalline TiO2 . It is clearly demonstrated that the as‐prepared amount‐optimized nanocomposite exhibits exceptional visible‐light photocatalytic activities for CO2 conversion to CH4 and for H2 evolution, respectively by ≈28‐time (140 µmol g −1 h −1 ) and ≈31‐time (313 µmol g −1 h −1 ) enhancement compared to the widely accepted outstanding g‐C3 N4 prepared with urea as the raw material, along with the calculated quantum efficiencies of ≈4.92% and 2.78% at 420 nm wavelength. It is confirmed mainly based on the steady‐state surface photovoltage spectra, transient‐state surface photovoltage responses, fluorescence spectra related to the produced OH amount, and electrochemical reduction curves that the exceptional photoactivities are comprehensively attributed to the large surface area (85.5 m 2 g −1 ) due to the porous structure, to the greatly enhanced charge separation and to the introduced catalytic functions to the carrier‐related redox reactions by decorating MnO x and coupling Au‐TiO2, respectively, to modulate holes and electrons. Moreover, it is suggested mainly based on the photocatalytic experiments of CO2 reduction with isotope 13 CO2 and D2 O that the produced CO2 and H as active radicals would be dominant to initiate the conversion of CO2 to CH4 . Abstract : Porous g‐C3 N4 ‐based nanocomposites as efficient photocatalysts to convert CO2 and produce H2 are successfully fabricated by decorating sheet‐like nanostructured MnO x and subsequently coupling Au‐modified nanocrystalline TiO2, dependent on the porous structure, and the greatly enhanced charge separation with the introduced catalytic functions to the carrier‐related redox reactions, respectively by decorated MnO x and coupled Au‐TiO2 to modulate holes and electrons.